ASIC1a Promotes nucleus pulposus derived stem cells apoptosis through modulation of SIRT3-dependent mitochondrial redox homeostasis in intervertebral disc degeneration - Zhi-Gang Zhang; Liang Kang; Lu-Ping Zhou; Yan-Xin Wang; Chong-Yu Jia; Chen-Hao Zhao; Bo Zhang; Jia-Qi Wang; Hua-Qing Zhang; Ren-Jie Zhang; Cai-Liang Shen (Redox Report, 2025)
The death of human nucleus pulposus derived stem cells (NPSCs) is a key factor affecting the endogenous repair capability and degeneration of intervertebral discs (IVD). ASIC1a is thought to be closely associated with cells destiny in IVD degeneration (IVDD). However, its physiological and pathological roles in human NPSCs are unclear. In this study, we found that the content of ASIC1a increased with IVDD in both rats and human discs. In acidosis-treated NPSCs, the expression level of ASIC1a increased, accompanied by inhibition of cells viability and activation of mitochondrial apoptotic pathway. Additionally, ASIC1a overexpression activated the mitochondrial apoptotic pathway and increased the level of cellular and mitochondrial ROS in human NPSCs. Moreover, we demonstrated that the dysfunction of SIRT3-regulated mitochondrial redox homeostasis was involved in ASIC1a overexpression-induced apoptosis in human NPSCs. The in vivo experiments also demonstrated that the ASIC1a/SIRT3 pathway was involved in IVDD. Overall, these findings showed that ASIC1a disrupted mitochondrial function and aggravated mitochondrial oxidative stress by inhibiting the expression of SIRT3, which activated human NPSC apoptosis and aggravated IVDD. These findings provide new insights for the development of innovative treatment strategies for IVDD.HighlightsAcidosis inhibited human NPSCs activity and promoted apoptosis via mitochondria.ASIC1a promoted acidosis-induced apoptosis of human NPSCs.ASIC1a inhibited SIRT3 expression, aggravating mitochondrial oxidative stress.ASIC1a promoted IVDD via mitochondrial oxidative stress and apoptosis.